World Statistics Pocketbook 2009 - United Nations Department of Economic; Social Affairs (United Nations, 2010)
This handy pocketbook provides an easy-to-use international compilation of basic economic, social and environmental indicators for 216 countries and areas worldwide. It covers ovwe 50 key indicators in the areas of population and migration, food and agriculture, education, energy, international trade, international tourism, and environment. The layout provides an easy-to-view comprehensive statistical profile of each country or area and the notes on sources and definition provide a valuable guide for further research by the in-depth user of these statistics.